Business and development - Ananya Mukherjee Reed (IIMB Management Review, 2010)
Businesses now contribute to development through avenues other than the generation of employment and economic growth, such as corporate social responsibility initiatives, corporate accountability movements and alternative business models, using several partnership formats to deliver. A panel with representatives from leading corporations, NGOs, and a public sector bank discussed the changing nature of corporate power, responsibility and ownership, the greater congruence between the goals of business and society, and how their organisations were responding to the changes and opportunities.